Benzothiazole moiety liquid crystalline monomers containing schiff base-ester: thermal, mesomorphic and optical properties / Nur Syafiqah Farhanah Dzulkharnien - Nur Syafiqah Farhanah , Dzulkharnien (2018)
A series of Schiff base ester chromophore based liquid crystalline monomers with rigid core benzothiazole ring and methacrylate group as terminal groups was designed and synthesized via Schiff base formation reaction followed by Williamson etherification and esterification reactions. These monomers were differentiated from each other by varying the substituents (-CH3, -OCH3 and -OCH2CH3) at the sixth position on benzothiazole moiety. The chemical structures of the synthesized monomers were characterized and confirmed by spectroscopic techniques such as FTIR, 1H NMR and 13C NMR. Thermogravimetric analysis (TGA) was used to study the thermal stability as well as thermal properties of the synthesized monomers. The monomer with ethoxy substituent (M4) showed the highest thermal stability compared to other monomers by comparing the decomposition temperatures corresponding to 5% weight loss for each of the monomers. The mesomorphic behavior for all liquid crystalline monomers was studied by using differential scanning calorimetry (DSC) and polarized optical microscopy (POM). POM studies revealed that monomer with no substituent at the sixth position of benzothiazole ring exhibited nematic and smectic mesophases at 120.7 oC and 74.2 oC respectively, upon cooling. Meanwhile, monomers with -CH3, -OCH3 and -OCH2CH3, revealed only nematic mesophase at 108.4 oC, 109.1 oC and 119.8 oC accordingly, during heating scan. The mesophase textures from POM observation are supported by corresponding DSC results. These results suggest that the formation of mesophases and that the mesophase stability of monomers M1 - M4 were influenced by the terminal substituents. The effects of substituents, solvent polarity and temperature on the optical properties of monomers M1 - M4 were evaluated with UV-Vis and fluorescence spectroscopies. It was found that the absorption and emission maxima of the monomers were red-shifted by the influence of various strength of electron-donating groups on the sixth position of benzothiazole moiety. The fluorescence studies showed that the monomers M1 - M4 exhibited a range of emission band at 401-500 nm which can be categorized as violet-blue emission. Furthermore, an investigation on the effect of different solvents showed that all the monomers exhibited a polytonic behavior upon increasing solvent polarity for absorption spectra. This result was further discussed using Reichardt-Dimroth solvent scales, ET(30) and Kamlet-Taft solvent scales. The thermochromic behavior of these monomers was evaluated using fluorescence spectroscopy from 20 oC to 55 oC. The fluorescence intensity for all monomers was decreased with respect to increase in temperature without shifting their emission band.